Photodynamic antimicrobial chemotherapy of asymmetric porphyrin-silver conjugates towards photoinactivation of Staphylococcus aureus. Issue 4 (16th February 2020) - Shabangu, Samuel M.; Babu, Balaji; Soy, Rodah C.; Managa, Muthumuni; Sekhosana, Kutloano E.; Nyokong, Tebello
Abstract: Asymmetric mono-carboxy-porphyrins, (5-(4-carboxyphenyl)−10, 15, 20-tris(pentafluorophenyl)porphyrinato zinc(II) (1 ), 5-(4-carboxyphenyl)−10, 15, 20-triphenylporphyrinato zinc(II) (2 ) and 5-(4-carboxyphenyl)−10, 15, 20-tris(2-thienyl)porphyrinato zinc(II) (3 ), were linked to Ag nanoparticles (AgNPs ) through amide bonds and self-assembly (the latter only for 3 ). The porphyrins and conjugates were used for photodynamic antimicrobial chemotherapy (PACT) against Staphylococcus aureus . PACT uses singlet oxygen for antimicrobial activity. Complex 3 and its conjugates had higher singlet oxygen quantum yields and higher log reduction when compared with the rest of the porphyrins and corresponding conjugates. These high log reductions for 3 and its conjugate were attributed to the presence of sulfur groups whereby there was more interaction with the bacterial membrane. Graphical Abstract: